Routine use of optical coherence tomography in bioresorbable vascular scaffold implantation: insights on technique optimization and long-term outcomes. Issue 4 (June 2019) - Abdelaziz, Hesham K.; Abuomara, Hossamaldin Z.; Ali, Montasir H.; Eichhofer, Jonas; Patel, Billal; Saad, Marwan
Abstract : Background: Data from prior studies have shown increased risk of adverse outcomes with bioresorbable vascular scaffolds (BVS) compared with drug-eluting stents. Objective: The objective of this study was to study the long-term outcomes with routine use of optical coherence tomography (OCT) for optimization of BVS implantation. Patients and methods: Clinical, procedural, and outcome data were collected for all patients who received ABSORB BVS between February 2014 and March 2016 in our tertiary center ( n =86). Preimplantation and postimplantation OCT was performed in all cases. Outcomes of interest included acute device success and long-term clinical outcomes including cardiac mortality, target vessel myocardial infarction, ischemia-driven target lesion revascularization, and scaffold thrombosis. Results: A total of 86 patients were included (106 lesions, 115 BVS implanted). Mean age was 59.5±10.9 years, with 66% men. Mean lesion length was 25.2±15.6 mm and mean reference vessel diameter was 3.42±0.45 mm. Type B2/C accounted for 40% of the lesions. All scaffold implantations followed the predilation, proper sizing, and postdilation strategy. Of the 115 scaffolds analyzed, 11 (9.5%) required further intervention based on prespecified OCT endpoints. On multivariate regression analysis, complex coronary lesion (type B2/C) was the single independent predictor of OCT use in scaffold optimization (odds ratio=6.3, 95% confidence interval: 1.3–7.8, P =0.02). At a mean follow-up duration of 31±7.1 months, no cases of cardiac mortality, target vessel myocardial infarction, ischemia-driven target lesion revascularization, or scaffold thrombosis were reported. Conclusion: Operators may consider OCT use for optimization of BVS implantation particularly in patients with complex coronary lesions. Abstract : Supplemental Digital Content is available in the text.